Form and Function of Nomina in the Story of Si Bontar Mudar of Bakkara - Gaol, Elisabet Ibn; Simaremare, Juni Agus; Purba, Sintia; Tarihoran, Yuly (Universitas Stikubank (UNISBANK) Semarang, 2024)
The purpose of this study is to describe the form and function of nouns in the story of Sibontar Mudar of Bakkara. The type of research method used by the author is the literature method. Data collection techniques in this research are reading, recording, processing the content in the story. The source of data analysis that researchers use is the storybook